Analysis of Operating Cash Flow to Detect Real Activity Manipulation and Its Effect on Market Performance - Andreas, Andreas (International Journal of Economics and Financial Issues, 2017)
Deviating from normal business practices to manipulate reported income is defined as real earnings management (Rowchowdhury 2006). A firm can alter the level of accruals to obtain the desired level of a high stock price and/or earnings. The desire to achieve a high stock price and/or earnings to meet the earnings benchmark induces corporate managers to engage in earning management, inflating current earnings at the expense of the firms' economic values. To meet a certain earnings target, managers can wait until the year-end to use discretionary accruals to manage reported earnings. However, this strategy runs the risk that the amount of earnings that needs to be manipulated is greater than the available discretionary accruals because the discretion on accruals is bounded by GAAP (Barton and Simko 2002). Real activities manipulations are less subject to this constraint. The focus of this study is the real activities manipulations because the auditors and regulators are less likely to be concerned with such behaviors. The results suggest that firms are likely to engage in real activity manipulation through operating cash flow. Further analysis reveals that firms more likely to engage in real activity manipulation have higher market performance than do their counterpart. Keywords: operating cash flow, real activity manipulation, market performance JEL Classifications: M02, M4, M41